If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying h + -1h + 2h + -1h = 18 Combine like terms: h + -1h = 0 0 + 2h + -1h = 18 2h + -1h = 18 Combine like terms: 2h + -1h = 1h 1h = 18 Solving 1h = 18 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Divide each side by '1'. h = 18 Simplifying h = 18
| 5(u-1)-5=-5(-5u+4)-6u | | x+x+32=72 | | 8c-8c+3c-c=4 | | 70=70r-70 | | 4(5.5)+3(-2.5)=1 | | 7k-5k+5k=7 | | 18z+2z-8z-12z+3z=9 | | w=2(w-50) | | 3(6+5y)=2-(x+4) | | x^2lne=-lne | | 7u-5u=14 | | M^2-p^2=0 | | 10w-95=95 | | w(w+3)=108 | | y=2(y-12) | | 3r+6r=9 | | 3r+6r=16 | | y+37=2y | | 4d+2=42 | | 5w-2w=18 | | 10p-5p=20 | | 2d-d=12 | | q=2(q-19) | | 1/3x=12.85 | | p=2(p-26) | | 18x-24=36-2x | | 10=2/5xn | | q=2(q-41) | | 10=2/5n | | 6m^2-m-7=0 | | X-v=-27+48 | | (13+-2x)4+-2x=16 |